‘Keeping it reel’: a focus on the working lives of Australian independent filmmakers - Ingersoll, Louise Phillipa (Curtin University, 2023)
This thesis explores the realities of work and employment for independent filmmakers as an issue of sustainability for the Australian screen industry. Using in-depth interviews with 24 participants the study applies critical realism and thematic analysis to examine the link between systems, structures and agency via an intensive empirical analysis of filmmakers’ working lives. The findings revealed a complex interplay between individuals and the open system in which they attempt to sustain a career.